Predictive Role of P Wave Duration, Amplitudes and P Wave Morphology in Preeclamptic Pregnant Women in the Third Trimester of Pregnancy - Edebiri O.E; Nwankwo A. A; Akpe P. E; Mbanaso E.L; Obiesi C. N; Orunta E.D (International Journal of Health and Medicine, 2025)
The ultimate goal of predicting preeclampsia that can enhance early detection and risk stratification in pregnant women, by leveraging the diagnostic potential of ECG patterns, we hope to improve maternal and fetal outcomes and contribute to the development of personalized care strategies for preeclamptic patients. Current diagnostic methods for preeclampsia rely primarily on routine blood pressure monitoring and proteinuria assessment, which have limited sensitivity and specificity. The aim of this study is to investigate the predictive role of P wave duration, amplitudes and morphology in preeclamptic pregnant women during the third trimester. Fourty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. These subjects consisted of twenty (20) normotensive and twenty (20) preeclamptic pregnant women in their third trimester of pregnancy. After the subjects were identified and recruited into the study, they were taken to the laboratory where their vital signs was taken and their ECG patterns recorded with ECG machine. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. Results from this present study show statistically significant increases in P wave duration, amplitude and abnormal M pattern among preeclamptic compare to normotensive pregnant women, consistent with prior research, abnormal M pattern in P wave morphology is linked to atrial pathology in preeclampsia. The study underscores the multifactorial nature of cardiovascular changes in preeclampsia and highlights the potential of ECG parameters in aiding early detection, risk stratification, and management of the condition.